EMOTIONAL INTELLIGENCE AND PARENTAL SUPPORTIVENESS AS PREDICTORS OF STUDENTS ACHIEVEMENT IN SENIOR SECONDARY SCHOOL FINANCIAL ACCOUNTING - Lukman, Adeola Kiadese; Omotayo, Bolarinwa Kayode (Sokoto Educational Review, 2020)
This study investigated Emotional Intelligence and Parental supportiveness as Predictors of Students’ achievement in senior secondary Financial Accounting using descriptive research design of correlation type. A total of Two hundred SS II financial accounting students selected through purposive sampling technique participated in the study. Three research questions were raised and answered at .05 level of significance. Two validated instruments-, emotional intelligence and parental involvement rating scale (EIPRS) and financial accounting achievement test (FAAT) were the major instruments used for data collection. The Pearson moment correlation and multiple regressions were the statistical tools used for data analysis. Findings from the study revealed that both emotional intelligence and parental supportiveness predict students’ achievement in financial accounting. It was recommended among others that counselors and teachers should work on the emotional wellbeing of the students in the school, while parent should be positively disposed to the academic pursuit of their children.